PEMODELAN PENURUNAN TANAH DI IBU KOTA NEGARA NUSANTARA MENGGUNAKAN ANALISIS NUMERIK METODE ELEMEN HINGGA LISA V.8 - Aco Wahyudi Efendi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
The IKN area is dominated by hilly areas and broad plains, Seeing the various soil characteristics and varying land elevations, disasters such as landslides and land subsidence often occur. This study validates the results of LISA against a geotechnical analysis program that is very often used and specifically for geotechnical software. It is hoped that the results of this study can contribute to the geotechnical world, especially to become a new treasure using the finite element method LISA. Forr the point of view the settlement that occurs is 0.0623 meters, where at analysis using geotechnical software, the settlement that occurs at the same point in the review is 0.0633 meters, there is an insignificant difference with a ratio of 1.016 from the results of the geotechnical software with the results of LISA V.8 FEA.